Negative active material and preparation method thereof, negative plate, battery and electric equipment
By using a combination of carbon matrix and polymer cladding in the negative electrode material of lithium-ion batteries, the problems of low efficiency and poor cycle stability of existing battery negative electrode materials are solved, and higher battery performance and longer service life are achieved.
Patent Information
- Application Number
- CN202411504993.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-04-08
AI Technical Summary
The negative electrode materials of existing lithium-ion batteries have low efficiency and poor rate performance and cycle stability during the first charge and discharge, resulting in rapid decline in battery capacity.
Using a negative electrode active material including a carbon matrix and a polymer cladding layer coated on the surface of the carbon matrix part, a stable cladding layer is formed by polymerization of specific monomers, improving the cyclic performance of the material and the first-time Coulomb efficiency.
It significantly improves the first-time Coulomb efficiency, rate performance and cycle stability of the battery and extends the service life of the battery.
Smart Images

Figure CN119786549A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a negative electrode active material, in particular to a negative electrode active material and a preparation method thereof, a negative electrode sheet, a battery and an electrical device, and belongs to the field of secondary batteries. Background Art
[0002] In recent years, with the rapid expansion of new energy in the power and energy storage markets, lithium-ion batteries have become the main energy supply form for portable electronic devices, electric vehicles and energy storage stations due to their high specific capacity and high energy density. At present, the negative electrode materials of lithium-ion batteries mainly include transition metal oxides, alloys and graphite. Graphite has low cost and strong lithium insertion ability. It can be used as a lithium ion intercalation receptor to form binary or ternary intercalation compounds, and has become the standard negative electrode material for lithium-ion batteries.
[0003] Among them, natural graphite has the advantages of low cost, high conductivity and large capacity, but there are a large number of voids and defects on the surface of natural graphite, resulting in a large specific surface area and many exposed active sites, which consumes a large amount of active lithium during the first charge and discharge, and has a low coulombic efficiency; in addition, the interface of natural graphite is extremely unstable during the cycle, and will continue to react with the electrolyte, consuming a large amount of active lithium, thereby causing the battery capacity to decline rapidly.
[0004] Therefore, developing negative electrode materials that can improve the battery's initial coulombic efficiency, rate performance and cycle stability has become a technical problem that needs to be urgently solved in this field. Summary of the invention
[0005] The invention provides a negative electrode active material. The negative electrode active material is used for a battery and can significantly improve the first coulombic efficiency, rate performance and cycle stability of the battery.
[0006] The present invention also provides a method for preparing a negative electrode active material. The preparation method has a simple process, and the prepared negative electrode active material can significantly improve the first coulombic efficiency, rate performance and cycle stability of the battery.
[0007] The present invention also provides a negative electrode sheet, which includes the negative electrode active material and is used in a battery to significantly improve the initial coulombic efficiency, rate performance and cycle stability of the battery.
[0008] The invention also provides a battery having excellent first coulombic efficiency, rate performance and cycle stability.
[0009] The invention also provides an electrical device with excellent performance.
[0010] In one aspect, the present invention provides a negative electrode active material, comprising a carbon substrate and a coating layer coated on at least a portion of the surface of the carbon substrate, wherein the coating layer comprises a polymer obtained by polymerization of monomers represented by Formula 1 and / or Formula 2;
[0011]
[0012] In Formula 1 and Formula 2, X1 and X2 are each independently selected from at least one of H, alkyl, and aromatic groups; X3 and X4 are each independently selected from at least one of H, halogen, C1-C6 alkyl, aromatic groups, or C1-C6 alkenyl groups.
[0013] The negative electrode active material as described above, wherein the monomer shown in Formula 1 includes one or more of vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 4,5-dimethyl-1,3-dioxol-2-one, 4,5-dibenzyl-1,3-dioxol-2-one, and 4,5-diphenyl-1,3-dioxol-2-one;
[0014] And / or, the monomer represented by formula 2 includes one or more of ethylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, bisfluoroethylene carbonate, (divinyl)ethylene carbonate, and propylene carbonate.
[0015] The negative electrode active material as described above, the molecular weight range of the polymer is Mw≤4.8×10 5 , preferably, Mw is 2000-10000.
[0016] The negative electrode active material as described above, wherein the coating layer further comprises a lithium salt;
[0017] Preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate;
[0018] More preferably, the mass ratio of the lithium salt to the carbon matrix is not higher than 5:100.
[0019] The negative electrode active material as described above, wherein the specific surface area of the carbon matrix is 7-9 m 2 / g.
[0020] The negative electrode active material as described above, wherein the coating layer has a thickness of 5-50 nm;
[0021] And / or, the mass ratio of the coating layer to the carbon matrix is not higher than 5:100.
[0022] In the negative electrode active material as described above, the carbon matrix includes one or more of natural graphite, artificial graphite, hard carbon material, silicon-carbon material, and mesophase carbon microbeads.
[0023] Another aspect of the present invention provides a method for preparing the negative electrode active material as described above, comprising the following steps:
[0024] A carbon matrix is added to a mixed system including the monomers shown in Formula 1 and / or Formula 2 and an initiator to initiate a polymerization reaction to obtain the negative electrode active material.
[0025] The preparation method as described above, wherein the polymerization reaction temperature is 50-70°C and the time is 12-25h;
[0026] And / or, the solvent of the polymerization reaction is selected from one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Preferably, the mass of the monomer is 5% to 15% of the mass of the solvent.
[0027] In the preparation method as described above, the initiator comprises one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and azobisisobutyramidine hydrochloride;
[0028] Preferably, the mass of the initiator is 0.4% to 2% of the mass of the monomer.
[0029] The preparation method as described above, wherein the mixed system further comprises a lithium salt;
[0030] Preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate.
[0031] In another aspect, the present invention provides a negative electrode sheet, comprising the negative electrode active material as described above or the negative electrode active material prepared by the preparation method as described above.
[0032] Another aspect of the present invention provides a battery, comprising the negative electrode sheet as described above.
[0033] Another aspect of the present invention provides an electrical device including the battery as described above.
[0034] The negative electrode active material provided by the present invention comprises a carbon matrix and a coating layer coated on at least part of the surface of the carbon matrix, wherein the coating layer is obtained by polymerization of a specific monomer. When the negative electrode active material is used in a battery, it can significantly reduce the interface impedance, improve the initial coulombic efficiency and improve the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 HRTEM test spectrum of the negative electrode active material provided in Example 1 of the present invention;
[0036] Figure 2 FTIR test spectra of negative electrode active materials provided in Comparative Example 1 and Examples 1, 3 and 7 of the present invention;
[0037] Figure 3 HRTEM test spectrum of the negative electrode sheet prepared from the negative electrode active material provided in Example 3 of the present invention;
[0038] Figure 4 This is the XPS test spectrum of the negative electrode sheet prepared from the negative electrode active material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] In one aspect, the present invention provides a negative electrode active material, comprising a carbon substrate and a coating layer coated on at least a portion of the surface of the carbon substrate, wherein the coating layer comprises a polymer obtained by polymerizing a monomer represented by Formula 1 and / or Formula 2;
[0041]
[0042] In Formula 1 and Formula 2, X1 and X2 are each independently selected from at least one of H, alkyl, and aromatic groups; X3 and X4 are each independently selected from at least one of H, halogen, C1-C6 alkyl, aromatic groups, or C1-C6 alkenyl groups.
[0043] In detail, the negative electrode active material provided by the present invention is a material with a core-shell structure, wherein the core is a carbon matrix, and the shell is a polymer coating layer obtained by polymerization of monomers represented by Formula 1 and / or Formula 2, and the polymer coating layer covers at least a portion of the surface of the core.
[0044] After the negative electrode active material provided by the present invention is used in a battery, the initial coulombic efficiency and cycle performance of the battery can be significantly improved. The inventors have analyzed this and believe that the reason may be that, on the one hand, the carbonyl group in the monomer represented by Formula 1 and / or Formula 2 has a strong electronegativity and can form a strong binding force with the carbon matrix, so that the coating layer formed by the polymerization of the monomer represented by Formula 1 and / or Formula 2 can be evenly coated on the surface of the carbon matrix and is not easy to fall off during the cycle process, thereby improving the cycle stability of the battery. On the other hand, the polymer obtained by the polymerization of the monomer represented by Formula 1 and / or Formula 2 can effectively reduce the activity specific surface of the negative electrode active material, thereby reducing the side reactions during the initial charge and discharge process, reducing the initial capacity loss, and improving the initial coulombic efficiency. At the same time, the consumption of electrolyte additives is reduced, and the rate performance of the battery is improved.
[0045] Further, in a specific embodiment of the present invention, the monomer represented by Formula 1 includes one or more of vinylene carbonate (VC), methyl vinylene carbonate (MVC), ethyl vinylene carbonate (EVC), 4,5-dimethyl-1,3-dioxol-2-one (DMVC), 4,5-dibenzyl-1,3-dioxol-2-one, 4,5-diphenyl-1,3-dioxol-2-one, etc.;
[0046] And / or, the monomer shown in Formula 2 includes one or more of ethylene carbonate (EC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC), (divinyl) ethylene carbonate, propylene carbonate (PC), etc.
[0047] When the above-mentioned types of monomers are selected, not only can a stable polymer coating layer be formed to improve the cycle performance, first coulombic efficiency and rate performance of the negative electrode active material, but also because the above-mentioned types of monomers are electrolyte additives, when the coating layer has been pre-formed, the amount of the electrolyte additive can be appropriately reduced, and during the formation process, the same additive in the electrolyte can be in-situ polymerized into a film on the basis of the polymer, so that the film is more closely bonded to the carbon matrix, thereby reducing the interface impedance and further improving the first coulombic efficiency, rate performance and cycle performance.
[0048] Furthermore, in one embodiment of the present invention, the molecular weight of the polymer is in the range of Mw≤4.8×10 5 , preferably, Mw is 2000-10000.
[0049] Here, Mw refers to the mass average molecular weight of a polymer. Specifically, the Mw of a polymer can be measured by GPC (gel permeation chromatography).
[0050] It is understood that the molecular weight of the polymer can be adjusted by controlling parameters such as the amount of monomers involved in the polymerization reaction, reaction time, reaction atmosphere, etc. during the preparation process.
[0051] Specifically, the molecular weight of the polymer is preferably in the range of 2,000 to 10,000.
[0052] When the molecular weight of the polymer is within the above range, the coating layer has a looser structure and is more flexible, which effectively reduces the interface impedance, improves the ionic conductivity, and further improves the first coulombic efficiency and cycle stability of the battery.
[0053] Furthermore, in a specific embodiment of the present invention, the coating layer also includes a lithium salt; preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate; more preferably, the mass ratio of the lithium salt to the carbon matrix is not higher than 5:100.
[0054] The mass ratio of lithium salt to carbon matrix can be controlled by controlling the amount of raw materials added during the preparation process.
[0055] Among them, when the mass ratio of lithium salt to carbon matrix is not higher than 5:100, the lithium salt can be coated by the polymer layer. When it is higher than this value, the lithium salt is easy to leak out of the coating layer, affecting the coating effect.
[0056] Further, in a specific embodiment of the present invention, the specific surface area of the carbon matrix is 7-9m 2 / g.
[0057] The specific surface area of the carbon matrix can be detected by a common detection method in the art, such as a nitrogen adsorption-desorption method, a specific surface area and pore size analyzer detection method, and the like.
[0058] Specifically, the specific surface area of the carbon matrix includes but is not limited to 7m 2 / g, 7.2m 2 / g, 7.4m 2 / g, 7.6m 2 / g, 7.8m 2 / g, 8.0m 2 / g, 8.2m 2 / g, 8.4m 2 / g, 8.6m 2 / g, 8.8m 2 / g, 9.0m 2 / g or any range between them.
[0059] Furthermore, in a specific embodiment of the present invention, the thickness of the coating layer is 5-50 nm; and / or the mass ratio of the coating layer to the carbon matrix is not higher than 5:100.
[0060] The coating thickness in the present invention refers to the average thickness of the coating, which can be detected by conventional methods in the art.
[0061] Specifically, the thickness of the coating layer includes but is not limited to 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or a range between any two of them.
[0062] When the coating layer thickness is within the above range, the formed coating layer is neither too thick to increase the battery impedance and reduce the capacity, nor too thin to completely cover the battery.
[0063] The mass ratio of the coating layer to the carbon matrix includes but is not limited to 1:100, 2:100, 3:100, 4:100, 5:100 or a range between any two thereof.
[0064] When the mass ratio of the coating layer to the carbon matrix is within the above range, the coating layer will not account for too large a proportion, thereby reducing the capacity of the battery.
[0065] Furthermore, in a specific embodiment of the present invention, the carbon matrix includes one or more of natural graphite, artificial graphite, hard carbon material, silicon-carbon material, and mesophase carbon microbeads.
[0066] In detail, natural graphite can be selected from natural spherical graphite, carbon-coated natural graphite, waste recycled natural graphite, etc.
[0067] When the above-mentioned types of carbon matrix are selected, the first coulombic efficiency, rate performance and cycle performance of the battery can be further improved.
[0068] Another aspect of the present invention provides a method for preparing the negative electrode active material as described above, comprising the following steps:
[0069] A carbon matrix is added to a mixed system including monomers represented by Formula 1 and / or Formula 2 and an initiator to initiate a polymerization reaction to obtain a negative electrode active material.
[0070] In detail, the preparation method provided by the present invention is used to prepare the above-mentioned negative electrode active material.
[0071] In a specific embodiment, the monomers represented by Formula 1 and / or Formula 2, an initiator and a solvent are mixed to obtain a mixed system, and then a carbon matrix is added to the mixed system, and the monomers represented by Formula 1 and / or Formula 2 are in situ polymerized to form a coating layer covering at least a portion of the surface of the carbon matrix to obtain a negative electrode active material.
[0072] It can be understood that after the polymerization reaction, the negative electrode active material mixed solution is obtained, and a drying process is also included to obtain a solid negative electrode active material.
[0073] The present invention does not limit the specific method and parameters of the drying process, and appropriate methods and parameters can be selected according to actual conditions.
[0074] In a specific embodiment, the negative electrode active material mixed solution obtained after the polymerization reaction is spray dried, with the inlet temperature set to 120° C. and the outlet temperature set to 90° C., and then cooled to obtain a solid negative electrode active material.
[0075] The negative electrode active material prepared by the preparation method provided by the present invention has excellent first coulombic efficiency and cycle stability when used in a battery, and has low preparation cost and simple operation.
[0076] Furthermore, in a specific embodiment of the present invention, the polymerization reaction temperature is 50-70°C, and the time is 12-25h; and / or the polymerization reaction solvent is selected from one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and preferably, the mass of the monomer is 5% to 15% of the mass of the solvent.
[0077] Specifically, the mixed system including the carbon matrix, the monomer and the initiator is stirred under an inert gas atmosphere, heated to 50-70° C., and maintained for 12-25 hours to perform a polymerization reaction. The stirring speed can be selected according to actual conditions, for example, 700 r / min.
[0078] In order to make the polymer coating layer formed by the polymerization reaction more stable, the temperature may be raised to a certain temperature for insulation treatment after the polymerization reaction.
[0079] In a specific embodiment, the temperature is raised to 80° C. after the polymerization reaction and kept at this temperature for 10 hours.
[0080] During the polymerization reaction, the solvent can play a role in dissolving and mixing, controlling the reaction rate, and improving the uniformity of the reaction.
[0081] In one specific embodiment, the mass of the monomer is controlled to be 5%-15% of the mass of the solvent, for example, including but not limited to 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or the range composed of any two thereof.
[0082] When the monomer mass and the solvent mass meet the above relationship, it can ensure that the monomer concentration during the polymerization reaction is within an appropriate range, improve the stability of the polymerization reaction, and make the molecular weight of the polymer formed after the polymerization reaction within the range of 2000 to 10000.
[0083] Initiators are responsible for starting the reaction process in a polymerization reaction, activating monomer molecules by generating free radicals, ions or other active substances, so that they can react with each other and form a polymer chain. The selection and use of initiators can control the speed and conditions of the reaction, thereby affecting the properties of the final polymer. In a specific embodiment of the present invention, the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and azobisisobutyramidine hydrochloride;
[0084] Preferably, the mass of the initiator is 0.4% to 2% of the mass of the monomer.
[0085] In detail, the ratio of the mass of the initiator to the mass of the monomer includes but is not limited to 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0% or a range composed of any two thereof.
[0086] When the mass of the initiator and the mass of the monomer meet the above relationship, it is possible to start the polymerization reaction while avoiding side reactions, optimize the polymerization process, control the degree of polymerization of the polymer formed after the polymerization reaction, and thus optimize the performance of the negative electrode active material.
[0087] The inventors found that when the negative electrode active material provided by the present invention was tested by X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy, the presence of -CN groups could be detected, indicating that initiator residues would remain in the finished negative electrode active material, but the residues of the initiator would not have an adverse effect on the battery performance.
[0088] Furthermore, in a specific embodiment of the present invention, the mixed system also includes a lithium salt; preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate.
[0089] When the mixed system includes lithium salt, the coating layer of the negative electrode active material finally prepared includes lithium salt. The ion channel formed by the lithium salt can further improve the interfacial transmission capacity of lithium ions, reduce battery impedance, and improve battery performance.
[0090] Among them, a suitable lithium salt content can be selected. In a specific embodiment, the mass ratio of the lithium salt content to the carbon matrix is not higher than 1:100.
[0091] When lithium salt is included in the mixed system, the initiator remaining in the finished negative electrode active material reacts with the lithium salt to form Li3N and LiF during the formation stage, further improving the interfacial transport capacity of lithium ions, reducing the low-temperature impedance of the battery, and improving the power performance of the battery.
[0092] In another aspect, the present invention provides a negative electrode sheet, comprising the negative electrode active material as described above or the negative electrode active material prepared by the preparation method as described above.
[0093] Since the negative electrode sheet includes the negative electrode active material, it has excellent first coulombic efficiency and cycle stability after being used in a battery.
[0094] The negative electrode sheet of the present invention specifically comprises a negative electrode current collector and a negative electrode active layer formed of a negative electrode active material and arranged on the surface of the negative electrode current collector.
[0095] When preparing the negative electrode sheet, the negative electrode active material, the conductive agent and the binder can be dispersed in an appropriate amount of deionized water, and the mixture is stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the negative electrode active layer includes 70-99wt% of the negative electrode active material, 0.5-15wt% of the conductive agent, and 0.5-15wt% of the binder according to the mass percentage, and further includes 80-98wt% of the negative electrode active material, 1-10wt% of the conductive agent, and 1-10wt% of the binder.
[0096] Among them, the material of the negative electrode current collector can be at least one of copper foil, nickel foam, and copper foam; the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0097] Another aspect of the present invention provides a battery, comprising the negative electrode sheet as described above.
[0098] It is conceivable that the battery of the present invention includes, in addition to the above-mentioned negative electrode sheet, a positive electrode sheet, an electrolyte and a separator.
[0099] The present invention does not strictly limit the positive electrode active material in the positive electrode sheet, for example, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium manganese oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, lithium iron phosphate (LFP), lithium nickel manganese oxide, lithium-rich manganese-based materials, etc.
[0100] The present invention does not strictly limit the selection of the electrolyte, and may include one or more of the solvents commonly used in the current battery electrolyte, and the electrolyte lithium salts commonly used in the current electrolyte, for example: the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, cyclopentane, γ-butyrolactone, etc.; the lithium salt may be, for example, one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0101] The present invention does not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in current batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, or a diaphragm with a ceramic coating.
[0102] When preparing lithium-ion batteries, the positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery, and the battery is placed, formed and sealed for the second time to complete the preparation of the lithium-ion battery.
[0103] Another aspect of the present invention provides an electrical device including the battery as described above.
[0104] The present invention does not limit the specific types of electrical equipment, and may include electric vehicles, mobile phones, smart homes, robots, drones, electronic cigarettes, speakers, and any other equipment that requires batteries to power them.
[0105] The electrical equipment provided by the present invention comprises the above-mentioned battery, and thus has good electrochemical performance and cycle stability.
[0106] Hereinafter, the negative electrode active material provided by the present invention is described in detail through specific examples.
[0107] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0108] Example 1
[0109] The method for preparing the negative electrode active material provided in this embodiment comprises the following steps:
[0110] 1. Dissolve VC monomer in DMC solvent at a mass concentration of 5%, add initiator azobisisobutyronitrile (AIBN), accounting for 0.5% of the total mass of the monomer, mix evenly at room temperature to obtain a mixed system. Subsequently, add natural spherical graphite powder material to the above mixed system, the total amount of VC monomer accounts for 1% of the mass fraction of graphite powder, heat and stir under argon protection, the reaction temperature is 60°C, the speed is 700r / min, and the in-situ polymerization reaction is carried out for 24h, and then the temperature is raised to 80°C and kept for 10h to obtain a negative electrode material mixed solution.
[0111] 2. The graphite negative electrode material mixture is spray dried with an inlet temperature of 120° C. and an outlet temperature of 90° C., and then cooled to obtain a negative electrode active material.
[0112] Example 2
[0113] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0114] In step 1), the mass of VC monomer accounts for 3% of the mass of natural spherical graphite powder material.
[0115] Example 3
[0116] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0117] In step 1), azobisisobutyronitrile is replaced by azobisisoheptanonitrile, and the mass of azobisisoheptanonitrile accounts for 1% of the mass of VC monomer.
[0118] Example 4
[0119] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0120] In step 1), the polymerization reaction time was changed from 24 h to 12 h.
[0121] Example 5
[0122] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0123] In step 1), the temperature of the in-situ polymerization reaction is changed from 60°C to 70°C.
[0124] Example 6
[0125] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0126] In step 1), lithium salt LiFSI is also added to the mixed system, and the content of lithium salt accounts for 0.5% of the content of VC monomer.
[0127] Example 7
[0128] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0129] In step 1), the temperature of the in-situ polymerization reaction is changed from 60°C to 50°C.
[0130] Example 8
[0131] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0132] In step 1), the argon atmosphere is replaced with an air atmosphere.
[0133] Example 9
[0134] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0135] 2. The graphite negative electrode material mixture was vacuum dried at 120° C. for 12 h, and cooled to obtain the negative electrode active material.
[0136] Example 10
[0137] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0138] In step 1), the specific surface area of natural spherical graphite powder material is 9m 2 / g.
[0139] Embodiment 11
[0140] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0141] In step 1), the mass of VC monomer is 15% of the mass of solvent.
[0142] Example 12
[0143] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:
[0144] In step 1), the mass of the initiator is 2% of the mass of the VC monomer.
[0145] Embodiment 13
[0146] The method for preparing the negative electrode active material provided in this embodiment comprises the following steps:
[0147] 1. Dissolve the FEC monomer in DMC solvent at a mass concentration of 15%, add the initiator azobisisobutyronitrile, accounting for 2% of the total mass of the monomer, mix evenly at room temperature to obtain a mixed system. Subsequently, add the hard carbon material to the above mixed system, the total amount of FEC monomer accounts for 2% of the mass fraction of graphite powder, heat and stir under argon protection, the reaction temperature is 60°C, the speed is 700r / min, and the in-situ polymerization reaction is carried out for 24h, and then the temperature is raised to 78°C and kept for 11h to obtain a negative electrode material mixed solution.
[0148] 2. The graphite negative electrode material mixture was spray dried with an inlet temperature of 100°C and an outlet temperature of 85°C, and then cooled to obtain a negative electrode active material.
[0149] Embodiment 14
[0150] The method for preparing the negative electrode active material provided in this embodiment comprises the following steps:
[0151] 1. Dissolve the VEC monomer in DMC solvent at a mass concentration of 10%, add the initiator azobisisobutylamidine hydrochloride, accounting for 2% of the total mass of the monomer, mix evenly at room temperature to obtain a mixed system. Subsequently, add artificial graphite to the above mixed system, the total amount of VEC monomer accounts for 2% of the mass fraction of graphite powder, heat and stir under argon protection, the reaction temperature is 60°C, the speed is 700r / min, and the in-situ polymerization reaction is carried out for 24h, and then the temperature is raised to 78°C and kept for 11h to obtain a negative electrode material mixed solution.
[0152] 2. The graphite negative electrode material mixture was spray dried with an inlet temperature of 100°C and an outlet temperature of 85°C, and then cooled to obtain a negative electrode active material.
[0153] Comparative Example 1
[0154] The negative electrode active material provided in this comparative example is a natural spherical graphite powder material. The difference between comparative example 1 and example 1 is that there is no polymer artificial SEI layer on the surface of the final product, and the rest is the same as example 1.
[0155] Test Case
[0156] 1. The specific surface area of the negative electrode active materials in all embodiments and comparative examples is tested, and the degree of polymerization and thickness of the coating layer of the negative electrode active materials provided in all embodiments and comparative examples are tested, comprising the following steps:
[0157] (1) Specific surface area test: BET method (Brunauer-Emmett-Teller method)
[0158] Sample preparation steps: Grind the material into a uniform powder, ensuring that the particle size is appropriate and dry;
[0159] (2) Polymer molecular weight test: GPC test (gel permeation chromatography)
[0160] Sample preparation steps: select a suitable GPC instrument and chromatographic column, as well as a mobile phase suitable for the coating layer, such as an organic solvent or buffer solution, dissolve the material in the mobile phase, filter to remove impurities and insoluble particles, and then inject the processed sample into the instrument for testing;
[0161] (3) Thickness test: HRTEM test (high resolution transmission electron microscope)
[0162] The specific test results are shown in Table 1.
[0163] Table 1
[0164] Serial number <![CDATA[Specific surface area (m 2 / g)]]> Mass average molecular weight Mw Thickness(nm) Example 1 4.31 5000 20 Example 2 3.4 9000 30 Example 3 4.06 5500 25 Example 4 4.78 4000 15 Example 5 4.21 5000 22 Example 6 4.27 5000 25 Example 7 5.83 2500 12 Example 8 5.56 5000 18 Example 9 4.4 5000 20 Example 10 5.07 6000 23 Embodiment 11 3.3 10000 33 Example 12 4.01 6000 26 Example 13 4.2 6000 23 Embodiment 14 4.11 6500 25 Comparative Example 1 6.74 6500 26
[0165] 2. Electrochemical performance test
[0166] The negative electrode active materials in each embodiment and each comparative example were assembled into lithium ion button half-cells for electrochemical performance testing.
[0167] The assembly method includes the following steps: polymer artificial SEI graphite negative electrode material, carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a mass ratio of 96:1.5:1:1.5, and then added to water and stirred evenly to form a negative electrode slurry. The negative electrode slurry is evenly coated on the copper foil using a coating machine, and the electrode piece is placed in a vacuum drying oven at a temperature of 120°C for vacuum drying for 12 hours, and rolled to form a negative electrode. Subsequently, a CR-2025 button lithium-ion battery is assembled in a glove box filled with argon gas, with a lithium sheet as the negative electrode, a diaphragm made of polypropylene, an electrolyte solute of 1M LiPF6, and a solvent of a mixed solution of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), with a volume ratio of 1:1:1.
[0168] (1) First coulombic efficiency test: First charge at 0.05C constant current to 0.01V, then charge at constant voltage with a cut-off current of 0.02C, and then discharge at 0.05C constant current to 2.0V. Record the first charge capacity C0 and the first discharge capacity D0 from 0.01 to 2.0V, respectively. Calculate the first coulombic efficiency according to D0 / C0. The specific results are shown in Table 2.
[0169] (2) Rate performance test: Charge to 0.01V with a constant current of 0.05C, then charge at a constant voltage with a cut-off current of 0.02C, and then discharge to 2.0V with a constant current of 0.05C. Repeat the above steps three times, charge to 0.01V with a constant current of 0.2C, then charge at a constant voltage with a cut-off current of 0.05C, and then discharge to 2.0V with a constant current of 2C. The specific results are shown in Table 2.
[0170] (3) Cyclic performance test: Charge to 0.01V with a constant current of 0.05C, then charge at a constant voltage with a cut-off current of 0.02C, and then discharge to 2.0V with a constant current of 0.05C. Repeat the above steps three times, and then perform charge and discharge cycles at a rate of 0.5C with a charge and discharge interval of 0.01-2.0V. Repeat this charge and discharge cycle 200 times, and measure the discharge capacity Q1 at the first cycle and the discharge capacity Q200 at the 200th cycle. Calculate the capacity retention rate Q after 200 cycles according to the following formula.
[0171] Capacity retention rate Q = Q200 / Q1*100%, see Table 2 for specific results.
[0172] Table 2
[0173]
[0174] 3. Negative electrode active material / electrode characterization test
[0175] The characterization methods for the negative electrode active materials provided in the examples include TEM, HRTEM, FTIR, and XPS tests.
[0176] TEM test: The negative electrode active material provided in Example 1 was tested. The surface of the carbon substrate was uniformly coated with an amorphous coating layer with a thickness of 20 nm, wherein Figure 1 This is the HRTEM test spectrum.
[0177] FTIR test: Corresponding to Example 1, the surface of the negative electrode active material provided in Examples 1, 3, and 7 was tested, such as Figure 2 As shown, Figure 2 A in the equation corresponds to proportion 1, Figure 2 B in the embodiment corresponds to Example 1, Figure 2 C in corresponds to Example 7, Figure 2 D in the above corresponds to Example 3, and the following characteristic peaks are measured: 1787 cm-1: carbonyl C=O stretching vibration characteristic absorption peak; 1822 cm-1: carbon ring skeleton stretching vibration absorption peak; 1563 cm-1: -1 :C=C double bond stretching vibration characteristic absorption peak; 3174cm -1 :=CH stretching vibration characteristic absorption peak, proving the presence of unsaturated carbon; 1150cm -1 and 1095cm -1 : The absorption peaks of symmetrical and asymmetrical stretching vibrations of COC; the above infrared spectrum data can be judged that the product contains a carbon-carbon double bond, an ester group, and a carbon ring skeleton, which is basically consistent with the structure of vinylene carbonate.
[0178] Characterization method for negative electrode sheets in finished battery cells: HRTEM and XPS testing.
[0179] HRTEM test: The negative electrode sheet prepared according to the above method in Example 3 was tested. Figure 3As shown, the carbon matrix is uniformly coated with a 25nm thick amorphous coating layer. The lattice fringes of the SEI film inorganic matter generated after chemical formation can be detected at the interface between the carbon matrix and the coating layer, such as: LiF ((200) crystal plane, crystal plane spacing is 0.201nm, Li2O (111) crystal plane, crystal plane spacing is 0.267nm, Li2CO3 (311) crystal plane, crystal plane spacing is 0.223nm, Li3N (100) crystal plane, crystal plane spacing is 0.515nm).
[0180] XPS test: The negative electrode sheet prepared according to the above method in Example 1 was tested. Figure 4 As shown, it can be seen that there is a characteristic peak of poly(VC) at around 292eV on the C1s energy spectrum, a characteristic peak of LiF at around 684.5eV on the F 1s energy spectrum, a characteristic peak of LiF at around 56.1eV on the Li 1s energy spectrum, a characteristic peak of Li3N at around 397eV on the N 1s energy spectrum, and a characteristic peak of Li2O at around 54eV on the Li 1s energy spectrum.
[0181] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode active material, characterized in that: It comprises a carbon matrix and a coating layer coated on at least a part of the surface of the carbon matrix, wherein the coating layer comprises a polymer obtained by polymerization of monomers represented by Formula 1 and / or Formula 2; In Formula 1 and Formula 2, X1 and X2 are each independently selected from at least one of H, alkyl, and aromatic groups; X3 and X4 are each independently selected from at least one of H, halogen, C1-C6 alkyl, aromatic groups, or C1-C6 alkenyl groups.
2. The negative electrode active material according to claim 1, characterized in that The monomers shown in Formula 1 include one or more of vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 4,5-dimethyl-1,3-dioxol-2-one, 4,5-dibenzyl-1,3-dioxol-2-one, and 4,5-diphenyl-1,3-dioxol-2-one; And / or, the monomer represented by formula 2 includes one or more of ethylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, bisfluoroethylene carbonate, (divinyl)ethylene carbonate, and propylene carbonate.
3. The negative electrode active material according to claim 1 or 2, characterized in that: The molecular weight range of the polymer is Mw≤4.8×10 5 , preferably, Mw is 2000-10000.
4. The negative electrode active material according to any one of claims 1 to 3, characterized in that: The coating layer also includes a lithium salt; Preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate; More preferably, the mass ratio of the lithium salt to the carbon matrix is not higher than 5:
100.
5. The negative electrode active material according to any one of claims 1 to 4, characterized in that: The specific surface area of the carbon matrix is 7-9m 2 / g.
6. The negative electrode active material according to any one of claims 1 to 4, characterized in that: The thickness of the coating layer is 5-50nm; And / or, the mass ratio of the coating layer to the carbon matrix is not higher than 5:
100.
7. The negative electrode active material according to any one of claims 1 to 6, characterized in that: The carbon matrix includes one or more of natural graphite, artificial graphite, hard carbon material, silicon-carbon material, and mesophase carbon microspheres.
8. A method for preparing the negative electrode active material according to any one of claims 1 to 7, characterized in that: The following steps are involved: A carbon matrix is added to a mixed system including the monomers shown in Formula 1 and / or Formula 2 and an initiator to initiate a polymerization reaction to obtain the negative electrode active material.
9. The preparation method according to claim 8, characterized in that: The polymerization reaction temperature is 50-70°C and the time is 12-25h; And / or, the solvent of the polymerization reaction is selected from one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Preferably, the mass of the monomer is 5% to 15% of the mass of the solvent.
10. The preparation method according to claim 8 or 9, characterized in that: The initiator includes one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, and azobisisobutyramidine hydrochloride; Preferably, the mass of the initiator is 0.4% to 2% of the mass of the monomer.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The mixed system also includes a lithium salt; Preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate.
12. A negative electrode sheet, characterized in that: The invention comprises the negative electrode active material according to any one of claims 1 to 7 or the negative electrode active material prepared by the preparation method according to any one of claims 8 to 11.
13. A battery, characterized in that: Including the negative electrode sheet as claimed in claim 12.
14. An electrical device, characterized in that: Comprising the battery of claim 13.
Citation Information
Patent Citations
Negative electrode active material, preparation method of negative electrode active material, negative electrode material, negative electrode and lithium ion battery
CN107785562A
Preparation method of lithium ion battery anode slurry, lithium ion battery anode material, and lithium ion battery
CN109301192A
Preparation and application of in-situ polymerization coated modified silicon-based negative electrode material
CN113270586A
Organic coating layer, electrode active material containing same and lithium ion battery
CN113707883A
Electrolyte and lithium ion battery
CN117374396A